Fetal methylphenidate exposure induced ADHD-like phenotypes and decreased Drd2 and Slc6a3 expression levels in mouse offspring. (15th June 2021) - Aoki, Satoru; Kaizaki-Mitsumoto, Asuka; Hattori, Natsumi; Numazawa, Satoshi
Graphical abstract: Highlights: Fetal methylphenidate exposure increases spontaneous locomotor activity in adolescents mice. Fetal methylphenidate exposure decreases anxiety-like behavior in adolescent mice. Fetal methylphenidate exposure decreases Drd2 and Slc6a3 gene expressions in the striatum. Abstract: Methylphenidate (MPD) is used as a first-line treatment for attention-deficit/hyperactivity disorder (ADHD). The number of prescriptions for ADHD patients is increasing, suggesting that the number of fertile women using such medication might be also increasing. The purpose of this study was to clarify the effects of MPD exposure during the fetal period on infant development, behavior, learning, and memory in mice. Expression levels of candidate genes associated with ADHD were also determined in the brain of pups born to MDP-treated dams who were administered MPD orally at a dose of 2.5, 7.5, or 15 mg/kg daily from gestational day 1 to the day before delivery. Offspring aged 6–8 weeks were subjected to the spontaneous locomotor activity, elevated plus-maze, and passive avoidance tests and therapeutic treatments with MPD or atomoxetine. Fetal MPD exposure induced ADHD-like phenotypes, such as hyperactivity and impulsivity, in mouse offspring, which were suppressed by treatment with MPD and atomoxetine. These mice showed decreased Drd2 and Slc6a3 expression levels in the brain, which are often observed in ADHD model animals. Our results suggest that continuous use of MPD during pregnancy induces ADHD phenotypes in the offspring.